Cover Feature: Spatially Resolved Experiments to Monitor the Singlet Oxygen Initiated Oxidation of Lipid Droplets in Emulsions (ChemPhotoChem 7/2018). Issue 7 (2nd July 2018) - Banerjee, Chiranjib; Breitenbach, Thomas; Ogilby, Peter R.
Abstract : The Cover Feature illustrates a focused laser beam used to create a localized population of singlet oxygen at the edge of a lipid droplet in an oil‐in‐water emulsion. The resultant oxidation at the droplet surface is monitored using a fluorescent dye. More information can be found in the Article by C. Banerjee et al. onpage 586 in Issue 7, 2018 (DOI:10.1002/cptc.201800005 ).